Loyalitas Nasabah pada Bank Papua Cabang Yogyakarta - Nevri Bayage Bayage; Dyah Sugandini; Purbudi Wahyuni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2018)
This study aims to analyze the factors that affect customer loyalty to customers of Bank Papua Branch Yogyakarta. Customer loyalty in this research is influenced by trust, switching barriers and bank image. Respondents in this study are all students who have savings in Bank Papua branch of Yogyakarta and domiciled in Yogyakarta. This research is a survey research by using questionnaires. The analytical tool used for hypothesis testing is SEM-PLS. The results of data analysis show that trust has a significant positive effect on switching barriers and image. Trust has no significant effect on loyalty. Switching barriers affect loyalty. The image is not proven to have a significant effect on loyalty.